2020
DOI: 10.1155/2020/6518508
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficacy and Safety of Mesenchymal Stem Cells for Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a polymorphic, multisystemic autoimmune disease that causes multiorgan damage in which cellular communication occurs through the involvement of autoantibodies directed against autoantigen production. Mesenchymal stem cells (MSCs), which have strong protective and immunomodulatory abilities, are obtained not only from bone marrow but also from medical waste such as adipose tissue and umbilical cord tissue and have been recognized as a promising tool for the treatment of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 26 publications
3
36
0
Order By: Relevance
“…Studies have shown that providers do not tightly adhere to recommended dosing of GVHD with an average dose of 1.4 × 10 6 MSCs/kg and three total doses administered (range is 1-10 doses administered) [16]. With such varying doses in MSC treatments, adverse events might be expected in the comparatively higher-dosed infusion; but overall, studies have not shown signi cant adverse events, which is consistent with our observations [15][16]. There has been…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Studies have shown that providers do not tightly adhere to recommended dosing of GVHD with an average dose of 1.4 × 10 6 MSCs/kg and three total doses administered (range is 1-10 doses administered) [16]. With such varying doses in MSC treatments, adverse events might be expected in the comparatively higher-dosed infusion; but overall, studies have not shown signi cant adverse events, which is consistent with our observations [15][16]. There has been…”
Section: Resultssupporting
confidence: 85%
“…Furthermore, no standard dosing has been published for pediatric rheumatic disease. There have been a few studies investigating the clinical e cacy and safety of MSC treatment in adult SLE with intravenous doses ranging from 1 × 10 6 MSCs/kg/dose to 2 × 10 8 MSCs/kg/dose [15]. In this case series, the patients' dosing ranged from 1.2 × 10 6 MSCs/kg/dose to 6.5 × 10 6 MSCs/kg/dose.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous meta-analysis also found that MSCs reduce Scr levels, BUN levels, and proteinuria, as well as alleviate renal damage in animal models of AKI [ 43 ]. Lower proteinuria was also found in patients with SLE after MSC therapy [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are characterized by strong anti-inflammatory and immune-regulatory activities, improving the microenvironment of the body and promoting the endogenous repair of the host. The safety and efficacy of MSC therapy have been demonstrated in many clinical trials, especially in immune-mediated inflammatory diseases, such as graft-versus-host disease ( Hashmi et al, 2016 ) and systemic lupus erythematosus ( Zhou et al, 2020 ). Given the strong immune-regulatory capacity of MSCs, the team recruited seven patients with COVID-19 for MSC transplantation to explore the potential of MSCs to treat patients with COVID-19 by observing the changes in immune and inflammatory system functions and the occurrence of side effects within 14 days after transplantation ( Leng et al, 2020 ).…”
Section: Dna Vaccinementioning
confidence: 99%